Global genetic insight contributed by consanguineous Pakistani families segregating hearing loss. Issue 1 (18th November 2018) - Richard, Elodie M.; Santos‐Cortez, Regie Lyn P.; Faridi, Rabia; Rehman, Atteeq U.; Lee, Kwanghyuk; Shahzad, Mohsin; Acharya, Anushree; Khan, Asma A.; Imtiaz, Ayesha; Chakchouk, Imen; Takla, Christina; Abbe, Izoduwa; et al.
Abstract: Consanguineous Pakistani pedigrees segregating deafness have contributed decisively to the discovery of 31 of the 68 genes associated with nonsyndromic autosomal recessive hearing loss (HL) worldwide. In this study, we utilized genome‐wide genotyping, Sanger and exome sequencing to identify 163 DNA variants in 41 previously reported HL genes segregating in 321 Pakistani families. Of these, 70 (42.9%) variants identified in 29 genes are novel. As expected from genetic studies of disorders segregating in consanguineous families, the majority of affected individuals (94.4%) are homozygous for HL‐associated variants, with the other variants being compound heterozygotes. The five most common HL genes in the Pakistani population are SLC26A4, MYO7A, GJB2, CIB2 and HGF, respectively. Our study provides a profile of the genetic etiology of HL in Pakistani families, which will allow for the development of more efficient genetic diagnostic tools, aid in accurate genetic counseling, and guide application of future gene‐based therapies. These findings are also valuable in interpreting pathogenicity of variants that are potentially associated with HL in individuals of all ancestries. The Pakistani population, and its infrastructure for studying human genetics, will continue to be valuable to gene discovery for HL and other inherited disorders. Abstract : In this study, we utilized genome‐wide genotyping, Sanger and exome sequencing to identify 163 DNA variants in 41 previously reported hearing loss (HL) genes segregating in 321 Pakistani families. SLC26A4, MYO7A, GJB2, CIB2 and HGF were identified as the five most common genes in our cohort. Our study provides a profile of the genetic etiology of HL in Pakistani families, which will allow for the development of more efficient genetic diagnostic tools, aid in accurate genetic counseling and guide application of future gene‐based therapies.